EXamining the knowledge, Attitudes and experiences of Canadian seniors Towards influenza (the EXACT survey) - Melissa K. Andrew; Vladimir Gilca; Nancy Waite; Jennifer A. Pereira (BMC Geriatrics, 2019)
Abstract Background Older adults are at high risk for influenza-related complications including worsening frailty and function. We surveyed older Canadians to explore the impact of influenza and determine how influenza knowledge influences vaccination decision-making. Methods We disseminated an online survey through a national polling panel. The survey included questions about the respondents’ influenza vaccination practices and knowledge about influenza. Using validated measures, they reported their frailty and functional status prior to the 2016/17 influenza season, during illness (if applicable), and following the season. Regression analyses were used to examine predictors of poor functional outcomes. Results Five thousand and fourteen adults aged 65 and older completed the survey; mean age was 71.3 ± 5.17 years, 42.6% had one or more chronic conditions, 7.8% were vulnerable and 1.8% were frail. 67.9% reported receiving last season’s influenza vaccine. Those who rarely/never receive the influenza vaccine were significantly less likely to correctly answer questions about influenza’s impact than those who receive the vaccine more consistently. Of the 1035 (21.5%) who reported experiencing influenza or influenza-like illness last season, 40% indicated a recovery longer than 2 weeks, and one-fifth had health and function declines during this time. Additionally, 3.1% of those afflicted “never fully recovered”. Older age, significant trouble with memory and having influenza/ILI were among the independent predictors of persistent declines in health and function. Conclusions Given that frailty and function are important considerations for older adults’ well-being and independence, healthcare decision-makers must understand the potential for significant temporary and long-term impacts of influenza to make informed vaccine-related policies and recommendations.